2015
DOI: 10.1021/jp5117245
|View full text |Cite
|
Sign up to set email alerts
|

Unification of Two Different Melting Mechanisms of Nanovoids

Abstract: Void melting in solids is a very complicated process, while the mechanism is far from understood. In this paper, we studied the void melting in Pd and Si solids using a molecular dynamics simulation method. It is found that there exist two different melting mechanisms for nanovoid, nucleation melting and non-nucleation melting; although void melting in Pd follows the former mechanism, that in Si follows the latter (unless the nanovoid size decreases to a critically small value). For nucleation melting, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The stability of the melt layer on the void surface was studied in 24 . Molecular dynamics simulations were used to study the mechanism of melting in 16,[24][25][26][27] . However, the effect of the width of void surface (i.e., internal surface) on void melting remains unexplored, and currently the only way to study it is to utilize the PF approach.…”
mentioning
confidence: 99%
“…The stability of the melt layer on the void surface was studied in 24 . Molecular dynamics simulations were used to study the mechanism of melting in 16,[24][25][26][27] . However, the effect of the width of void surface (i.e., internal surface) on void melting remains unexplored, and currently the only way to study it is to utilize the PF approach.…”
mentioning
confidence: 99%
“…These quantities govern the performance of a substance such as the elastic modulus(energy density), [13] critical temperature for phase transition(cohesive energy), [14] chemical reactivity(bond energy). [15]…”
Section: Introductionmentioning
confidence: 99%
“…[12] Investigations revealed that variation of the shape, size, and doping of inert gases will change the properties of materials pronouncedly. Besides, the analysis also derives quantitative information of rare gas doping effect on the bond length, bond energy, energy density, and atomic cohesive energy of Li and Na crystals.These quantities govern the performance of a substance such as the elastic modulus(energy density), [13] critical temperature for phase transition(cohesive energy), [14] chemical reactivity(bond energy). [15]…”
mentioning
confidence: 99%